Patent Angiostrongylus mackerrasae infection in a black flying fox (Pteropus alecto). Issue 9 (27th August 2013) - Mackie, JT; Lacasse, C; Spratt, DM
<x xml:space="preserve">Abstract</x> Background A wild adult male black flying fox (Pteropus alecto) was presented unable to fly or hang strongly. Results Necropsy and histological examination revealed a severe pneumonia, with numerous Angiostrongylus mackerrasae in the pulmonary artery. The pulmonary parenchyma contained numerous eggs and rare larvae. Conclusion This is the first report of patent Angiostrongylus infection in an accidental (i.e. non‐Rattus) host species. It is also the first report of A. mackerrasae infection in an accidental host (including flying foxes). Worms recovered from cases of suspected angiostrongyliasis should be examined in morphological detail to ensure correct identification.